2005
DOI: 10.1242/dev.01862
|View full text |Cite
|
Sign up to set email alerts
|

Lineage restriction maintains a stable organizer cell population at the zebrafish midbrain-hindbrain boundary

Abstract: The vertebrate hindbrain is subdivided into segments, termed neuromeres,that are units of gene expression, cell differentiation and behavior. A key property of such segments is that cells show a restricted ability to mix across segment borders – termed lineage restriction. In order to address segmentation in the midbrain-hindbrain boundary (mhb) region, we have analyzed single cell behavior in the living embryo by acquiring time-lapse movies of the developing mhb region in a transgenic zebrafish line. We trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Therefore, the MHB boundary is coupled with the heritable expression of Gbx2 in r1 cells. Our findings are in agreement with a previous report that suggested that lineage restriction is probably established at the MHB at the end of gastrulation in zebrafish (Langenberg and Brand, 2005). A GIFM study using a Wnt1-CreER transgenic mouse line to label mes cells suggests that lineage restriction may not occur in either the alar plate until E8.5, or in the basal plate until E9.5 (Zervas et al, 2004).…”
Section: Previous Studies Have Demonstrated That Mutual Inhibition Besupporting
confidence: 93%
“…Therefore, the MHB boundary is coupled with the heritable expression of Gbx2 in r1 cells. Our findings are in agreement with a previous report that suggested that lineage restriction is probably established at the MHB at the end of gastrulation in zebrafish (Langenberg and Brand, 2005). A GIFM study using a Wnt1-CreER transgenic mouse line to label mes cells suggests that lineage restriction may not occur in either the alar plate until E8.5, or in the basal plate until E9.5 (Zervas et al, 2004).…”
Section: Previous Studies Have Demonstrated That Mutual Inhibition Besupporting
confidence: 93%
“…Besides the involvement of Otx proteins, the two signalling centres also each release a combination of signal molecules (ZLI: Wnt8b and Shh; MHB: Wnt1 and Fgf8). The boundary between the midbrain and hindbrain has lineagerestriction properties (Zervas et al, 2004;Langenberg and Brand, 2005), whereas the ZLI is a narrow stripe of cells defined by both an anterior and a posterior lineage-restriction boundary . Therefore, because the ZLI is a zone rather than an interface, we considered whether the position of its prethalamic border is set independently of its thalamic border.…”
Section: Independent Positioning Of the Anterior And Posterior Zli Bomentioning
confidence: 99%
“…In recent years, it has become increasingly clear that the boundaries of such lineage restriction compartments function as bi-directional signalling centres (Kiecker and Lumsden, 2005). Thus, for example, the midbrain-hindbrain boundary (Langenberg and Brand, 2005;Zervas et al, 2004) and the zona limitans intrathalamica (ZLI) ) pattern adjacent neuroepithelium. In this study, we used the precedent of the experimental approaches taken by these studies to determine whether such a signalling centre is maintained at the boundary between the roof plate and the neuroepithelium.…”
Section: Introductionmentioning
confidence: 99%